How to explore planets with drones. Issue 3 (1st June 2018) - Macdonald, Sofie; Stevens, Adam
Abstract : Sofie Macdonald and Adam Stevens discuss new options for exploration. Abstract : What could autonomous aircraft do for planetary exploration? Sofie Macdonald and Adam Stevens set out the potential and pitfalls of extraterrestrial drones.